EDITORIAL - Mosca, Dante H. (Revista de Engenharia Térmica, 2009)
This editorial focuses on the important contribution that engineering and science of materials have to offer in thermal engineering applications, in particular, energy management. The search for innovative technologies is more than ever crucial to meet many future energy needs around the world. One example is thin-film technology that continuously grows into the global research field, following recognition that the properties of thin surface layers differ greatly from those of the same materials in bulk. The effects of increased surfacearea, in tandem with quantum effects, begin to dominate material properties. The development of nano-materials research is expected to play an increasing role in sustainable technologies for energy conversion, storage and savings. Areas of interest include solar cells, batteries, fuel cells, thermoelectrics, superconductors, multiferroics, magnetocalorics, and more recently hydrogen technologies. Incremental improvements in most of the current technologies are not sufficient to address the important issues of efficiency, durability and costs. Novel materials and innovative manufacturing approaches are therefore needed to design, elaborate and integrate materials for energy applications. Among promising materials technologies stand out carbon-nanotubes and graphene, which are suitable for low power consumption integrated circuits and applications in electronics. Carbon-based nanostructures are also investigated for solid state storage of hydrogen. In another line of work, proton exchange membrane fuel cell technology has also received increased attention as an efficient and environmentally friendly means of power generation in both stationary and mobile applications. Nano-material combinations could provide the performance required for miniaturized batteries to store solar energy and power smart cards. The low-cost superconductor technology is other promising field. Wires of high temperature superconductors are necessary for applications in power generation, transportation, transformation and storage. Beyond the incorporation in the energetic network, superconductor materials are also a key to develop new medical technologies based on magnetic resonance imaging performed in high magnetic fields. An important step has been a recent demonstration of the possibility of mass manufacturing of low cost superconducting tapes with innovative methodologies for deposition from chemical solutions. Other innovative and promising processes are chemical vapor deposition of silicon nano-films and polymer coatings structured for solar cells and light-emitters, which are also potentially helpful for photovoltaics and optoelectronics. Within this nanotech revolution, there is an urgent need for more control and specific legislation against non-advised dissemination of nanomaterials. The properties and functionalities of specific nano-materials require long term studies for understanding their behavior in organisms and the environment. All these actions and initiatives involving materials are important and welcome because attract researchers from different fields, inspiring cooperation between multidisciplinary teams in Brazil.